Construction of full-scale trials to evaluate the performance of induced cracked CBM roadbases - 217551 Ellis, S. J.; Megan, M. A.; Wilde, L. A.; Transport Research Laboratory (Great Britain); Highways Agency (Berkshire : Transport Research Laboratory, 1997)
08